“Across the Shadowy Landscape of Memory”:: A Relational Reading of Liminal Traumas in Anita Rau Badami’s Can You Hear the Nightbird Call? - Llano Busta, Andrea (International Journal of English Studies, 2025)
Liminal trauma narratives provide access to the formal representation and the affective dimension of trauma. Anita Rau Badami’s multigenerational and transnational novel Can You Hear the Nightbird Call? (2006) is a case in point, in which in-betweenness is not merely a source of affliction but may develop into a stepping stone to a belated understanding of past tragedies in twentieth-century India and Canada. Through a relational and dialogical approach encompassing Indra’s net, postmemory, rhizomatic theory, and multidirectional memory, liminality is addressed in the family and historical spheres, tracing vertical and horizontal connections between characters and episodes, which, it is argued, challenge event-based models of trauma studies, stress the importance of emotional alliances, and promote the establishment of communities of memory. Ultimately, chronologies and hierarchies are discarded in favour of network arrangements as the most suitable way to deal with interconnected traumas.